Crack tip fields in elastic-plastic and mixed mode I+II+III conditions, finite elements simulations and modeling - F. Fremy,; S. Pommier; E. Galenne; S. Courtin (Fracture and Structural Integrity)
This paper is devoted to the analysis of the load path effect on I+II+III mixed mode fatigue crack propagation in a 316L stainless steel. Experiments were conducted in mode I+II and in mode I+II+III. The same maximum, minimum and mean values of the stress intensity factors were used for each loading path in the experiments. The main result of this set of experiments is that very different crack growth rates and crack paths are observed for load paths that are however considered as equivalent in most fatigue criteria. The experiments conducted in mode I+II and in mode I+II+III, also allowed to show that the addition of mode III loading steps to a mode I+II loading sequence is increasing the fatigue crack growth rate, even when the crack path is not significantly modified.